Research Notes - Donaldson, Lex (Academy of Management Journal, 1982)
The article presents a study which tested the hypothesis that companies with multidivisional structures are more likely to diversify in subsequent periods than those with functional structures. Data analyzed in the study are based on published studies of the structure and degree of diversification of large corporations in France, West Germany, Japan, Great Britain and the U.S. The results of the study revealed that divisionalization is not more conducive to subsequent diversification than is functional organization.